Social Piety and Care for Families Infected with Covid-19 in the Context of SDGs in the Kuyudan Makamhaji Muslim Community - Suharjianto; Kukuh Yudha Pratama; Andri Arungga Sweta; Ma’arif Jamuin; Ratna Sesotya Wedadjati (Universitas Muhammadiyah Surakarta, 2024)
Objective: This research was motivated by curiosity about the Muslim community of Gang Arjuna Kuyudan Makamhaji who understood and practised the verses concerning social concern for families infected with Covid-19. The verses in question are Q.S al-Maidah, 5:2 and Q.S al-Hasyr, 59:9. This study aims to investigate how the Muslims in Gang Arjuna acquire knowledge and understanding of Surah al-Maidah, 5:2 and al-Hasyr, 59:9, and how they practice these verses to assist Covid-19 infected families in both material and non-material forms. Theoretical Framework: The theoretical framework used in this study relates to social concern in Islam and its contribution to achieving the Sustainable Development Goals (SDGs), particularly those related to health and well-being. Literature Review: The literature review reveals that these verses teach the importance of mutual assistance and sharing with those in need, especially in crises such as the Covid-19 pandemic. Methods: The research method used is descriptive quantitative, employing closed questionnaires and Likert scale techniques. The number of respondents in this study was 20, but only 15 participated. Results: The results show that the Muslims in Gang Arjuna are very familiar with Surah al-Maidah, 5:2, and Surah al-Hasyr, 59:9, and they gain knowledge of these verses through reading the Qur'an and attending mosque studies. The people of Gang Arjuna also exhibit a high level of social concern for families infected with Covid-19, offering both material and non-material assistance, which is an implementation of their understanding of these verses. Implications: The implications of this research demonstrate that understanding the social values in Islam can strengthen social solidarity and support the achievement of SDGs, particularly in the context of health and community empowerment. Novelty: The novelty of this study is its emphasis on the practical application of Qur'anic verses as a form of social concern in the face of the Covid-19 pandemic.